Storytime magic 400 fingerplays, flannelboards, and other activities - MacMillan, Kathy 1975-; Kirker, Christine (Chicago American Library Association, 2009)
Provides a generous sampling of art and craft ideas, songs, and action rhymes, designed to help veteran librarians refresh and enliven ongoing programs, while providing novice storytime planners what they need to get started.
Storytime tips for every age group--All about me--Animals--Around the world--At home--Bugs and insects--Concepts--Fairy tales and castles--Family and friends--Food--Holidays and celebrations--The natural world--People in my neighborhood--Play--School and library--Sing and dance--Transportation.
Keywords: Children's libraries